2015
DOI: 10.14419/ijans.v4i2.4877
|View full text |Cite
|
Sign up to set email alerts
|

Suspended liminality: breastfeeding and becoming a mother in two NICUs

Abstract: <p><strong>Objectives:</strong> This paper presents the results of an ethnographic study of breastfeeding and mothers’ experiences within two neonatal intensive care units (NICU).</p><p><strong>Methods:</strong> The data collection involved 135 hours of participant observation over a 6-month period and semi-structured interviews of 17 mothers.</p><p><strong>Results:</strong> Data analysis showed that the mothers faced many obstacles that prohibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…When physical contact is barely possible, child-parent interaction is relatively nonreciprocal. Shattnawi (2015) revealed that this physical distance is extremely stressful for mothers. Flacking et al (2006) illustrated how mothers felt "they had become mothers physically but not socially or emotionally" (p. 73).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…When physical contact is barely possible, child-parent interaction is relatively nonreciprocal. Shattnawi (2015) revealed that this physical distance is extremely stressful for mothers. Flacking et al (2006) illustrated how mothers felt "they had become mothers physically but not socially or emotionally" (p. 73).…”
mentioning
confidence: 99%
“…First, studies show that parents who experience the birth of an extremely preterm baby do not feel mentally prepared for this situation (Hall, Kronborg, Aagaard, & Brinchmann, 2013). They enter a world foreign to them, encountering the NICU, with its sounds, incubators, wires, and tubes, as a highly technologized environment (Cleveland, 2008; Hutchinson, Spillett, & Cronin, 2012; Lundqvist, Nilstun, & Dykes, 2002; Shattnawi, 2015; Shin & White-Traut, 2007). This open space immediately “signal[s] life and death” (Flacking et al, 2006, p. 73).…”
mentioning
confidence: 99%
“…While this physical separation may be considered a necessary standard of care by the institution and its providers, it represents a likely unconscious disregard for, and further separation of, the emotional needs of mothers and their infants in favour of their perceived overriding physiological needs (Dykes & Flacking, ). This separation also has direct repercussions on breastfeeding as it can delay and deplete milk creation (Shattnawi, ).…”
Section: Discussionmentioning
confidence: 99%
“…For parents of preterm (born ≤37 weeks’ gestation) or critically ill infants, an added layer of complexity is affixed to decisions around infant feeding. The subsequent admission to the neonatal intensive care unit (NICU) is typically unexpected and involves forms of medical intervention far beyond what is anticipated in the “typical” birth of a baby (Shattnawi, ). Breastfeeding and/or provision of expressed breast milk can take on a whole new meaning within the NICU environment.…”
Section: Introductionmentioning
confidence: 99%
“…The acuity and highly technical realm of the neonatal intensive care unit creates a complex environment for both care providers and families. Admission of a preterm and/or critically ill infant to the NICU is typically an unexpected event for parents (Shattnawi, 2015), posing unique stressors and altering the birthing experience from what is often anticipated in the days and months leading up to a 'typical' birth. Existing neonatal literature has established that the experiences of parents of preterm and/or critically ill infants differs from those of healthy, term infants and that NICU admission elicits feelings of heightened anxiety, emotional and psychological distress (Boykova, 2016;Bicking & Moore, 2012).…”
Section: Infant Feeding In the Nicumentioning
confidence: 99%